PENERAPAN PEMBELAJARAN AL-QUR’AN HADITS BERBASIS MULTILITERASI PADA MASA PANDEMI QIF-19 DI MADRASAH TSANAWIYAH NAILUS SYUKRI GEDEG MOJOKERTO - Rahmat (Jurnal Studi Islam Lintas Negara (Journal of Cross-Border Islamic Studies), 2020)
The multiliterative learning model is a learning model that maximizes the conception of language literacy in order to optimize cognitive, affective and psychomotor abilities in various scientific disciplines. With this in mind, mastery of languages ​​will be very useful as an initial ability to master the subject matter. Language literacy skills include listening, speaking, reading, and writing skills. In practice, this model will be applied with a variety of language learning methods which are specifically designed to be used in the mastery of certain scientific disciplines. Therefore this paper will analyze the multiliteration learning model in the Al-Qur'an Hadith learning. The use of relevant research methods is a descriptive qualitative approach with the type of case study at Madrasah Tsanawiyah Nailus Syukri Gedeg Mojokerto. Whereas the results of this study resulted in a multiliterative learning model with the Idea Stimulation Method which was very appropriate to be applied in online learning during the Qif-19 pandemic which could not be predicted with certainty, but learning activities must continue to run in order to carry out the mandate of national education.